Borrowing As A Tool To Fill The Ideological Thoughts: The Role Of Code-Mixing In An American Brat By Bapsi Sidhwa And The Escape By Qaisra Shiraz - Mirza Noman Shamas (University of Chitral Journal of Linguistics and Literature, 2019)
This research article highlights the temperament, inference, scope, and motives of code mixing in Pakistani English works. One novel from Pakistani English novels namely, An American Brat by Bapsi Sidhwa and one short story namely, The Escape by Qaisra Shehraz are being selected as an illustration of this reading. In this novel and short story the writers have already dealt with the characteristics of post colonialism. English language and literature pierced into the privileged civilizations of the sub-continent, after the end of British Imperialism. Pakistani writers in English are the best interpreter of the post-colonial communal language. In this study, I have hit upon code mixing in English works written by Pakistani authors to a bigger echelon. These works are paragons of arts and the unbelievable mixture of rhetorical and fictitious study. In these works the writers have not abased the confined diversities. They have tinted the value of Pakistani English in order to achieve the chatty desires of native people. These borrowings from the native languages are used to fill the lexical fissures of ideological thoughts. The reason of these borrowings is not to represent the English as substandard assortment. Through the utilization of native words we conclude that the significance of native languages has been tinted to question mark the dialect as well. The words of daily use also have an area of research for English people without having any substitute in English. That’s why in English literature innovative practices and ideas of code-mixing have been employed.